Three new species of Freycinetia (Pandanaceae) from Kalimantan, Indonesia - Keim, Ary Prihardhyanto (Research Center for Biology, 2009)
Three new species of Freycinetia (Pandanaceae) from Kalimantan (Indonesian Borneo) are firstly described in this paper namely F. kartawinatae A.P. Keim, F. runcingensis A. P. Keim, and F. subracemosa A.P. Keim.